Analisis Keaktifan Siswa pada Organisasi Siswa Intra Sekolah (OSIS) dalam Meningkatkan Prestasi Belajar Siswa di SMP Negeri 3 Mataram - Faqih, Muhammad; Suhardi, Muhammad; Hakim, Lukman; Ramadani, Deanti Triana (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2023)
This study aims to find out: 1) a description of student activity in the Intra-School Student Organization (OSIS) at SMP Negeri 3 Mataram, 2) a description of student achievement at SMP Negeri 3 Mataram, 3) the effect of activeness on the Intra-School Student Organization (OSIS) on student achievement at SMP Negeri 3 Mataram. The research approach used is quantitative, with a sample of 69 students who are members of the Student Council. Data collection was carried out using documentation and questionnaire techniques. The collected research data were then analyzed using descriptive statistical techniques and simple regression, to test the research hypothesis. The results of the analysis show: 1) Based on the results of the correlation test, the value of r-count (0.036) > r-table (0.001) is obtained, which means that there is an insignificant relationship with a moderate level between the variables of student activity and learning achievement; 2) The resulting regression equation Y = 82.046 + 0.258 (X); 3) The effect of student activeness (X) on learning achievement (Y) is an insignificant effect, based on t-test = 0.297 with a significance level of 0.768; 4) The results of the Simultaneous Test (F Test) show the value of F-count = 0.088 with a significant level of 0.768 which means that the prediction of student learning outcomes using student activity is not an accurate prediction; and 5) Based on the test of the coefficient of determination, the value of R = 0.036 can be interpreted that there is a large influence of student activeness on learning achievement which is 3.6%.